2005
DOI: 10.1074/jbc.c400487200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Heat Shock Gene Expression by RNA Polymerase II Elongation Factor, Elongin A

Abstract: The elongation stage of transcription by RNA polymerase II (Pol II) has emerged as an essential regulated step. Elongin A (EloA) is the largest subunit of the Elongin complex that can increase the catalytic rate of mRNA synthesis by Pol II. We recently demonstrated that the Elongin A homologue in Drosophila, dEloA, is essential and has properties consistent with those of a Pol II elongation factor in vivo. The goal of this study was to test whether dEloA is required for heat shock gene transcription, since hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Paused RNA Pol II has been best characterized as a regulatory point at heat-shock loci in Drosophila, where RNA Pol II sits in an engaged state at the promoter, nonproductively transcribing ;25 nucleotides (nt) in the nonstressed state. Upon heat shock, Pol II is released for the production of full-length transcripts (Gilmour and Lis 1986;Rougvie and Lis 1988;Gerber et al 2001Gerber et al , 2005Smith et al 2008b). …”
mentioning
confidence: 99%
“…Paused RNA Pol II has been best characterized as a regulatory point at heat-shock loci in Drosophila, where RNA Pol II sits in an engaged state at the promoter, nonproductively transcribing ;25 nucleotides (nt) in the nonstressed state. Upon heat shock, Pol II is released for the production of full-length transcripts (Gilmour and Lis 1986;Rougvie and Lis 1988;Gerber et al 2001Gerber et al , 2005Smith et al 2008b). …”
mentioning
confidence: 99%
“…Loss of CDK9 activity is followed by a substantial decrease in the association of other essential Pol II elongation factors such as FACT; however, p21 gene expression is not altered in their absence. Recently, several RNA Pol II elongation factors, such as ELL and Elongin A, were found to be required for proper cellular response to heat shock (Gerber et al 2005). It will be interesting to uncover whether such Pol II elongation factors that regulate the elongation stage of transcription are required for proper p21 gene expression.…”
Section: Drb Treatment Induces P21 Expression In the Absence Of P-tefmentioning
confidence: 99%
“…8,13,14 Although the functions of Elongin A in vivo remain largely unclear, Gerber et al 15 have recently reported that the Drosophila homolog of Elongin A (dEloA) colocalizes with pol II at sites of active transcription on polytene chromosomes, and it also plays a critical role in heat shock gene expression in vivo. 15,16 Moreover, by the RNA interference (RNAi) knockdown of dEloA, they have also shown it to be an essential factor required for proper metamorphosis, although the relationship between the elongation activity and viability remains unclear.To gain more insight into the physiological functions of Elongin A, we have generated Elongin A-deficient mice. Elongin A À/À embryos exhibited severe growth retardation and died at between days 10.5 and 12.5 of gestation, most likely owing to excessive apoptosis.…”
mentioning
confidence: 99%